Bridging the Gap in Speaking: Local Folktales as a Strategy for Active Participation in EFL Education - Amriani Hambali; Marlini Novianty (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study investigates the use of local folktales as a culturally responsive strategy to enhance students’ active participation and confidence in English speaking classes. The research was conducted as a one-shot descriptive case study involving 15 students from a junior high school in the Selayar Islands, Indonesia. Over five sessions, students participated in a series of folktale-based speaking activities, including discussion, retelling, word shopping, and role play. Data were collected through classroom observations, video recordings, and a perception questionnaire. The findings revealed that folktales effectively encouraged students to speak more actively, ask questions, and express opinions, particularly during discussion and role-play activities. Students reported high levels of enjoyment and motivation, attributing their increased confidence to the familiarity and moral values of the stories. Although participation was lower in retelling tasks, the overall results highlight the potential of culturally grounded materials to foster communicative engagement and reduce speaking anxiety. Despite its limited scope and duration, this study provides pedagogical insights into integrating local narratives in EFL classrooms to make learning more meaningful and culturally relevant.